2017
DOI: 10.1126/sciadv.1602506
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein-linked DNA breaks perturb mitochondrial gene transcription and trigger free radical–induced DNA damage

Abstract: Mitochondrial protein-linked DNA repair promotes gene transcription and protects from free radical–induced DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 75 publications
4
52
0
1
Order By: Relevance
“…This result was supported by our further observation that mtDNA 8-OHdG positively correlated with coronary stenosis severity, as determined by the number of diseased vessels and modified Gensini scores. Indeed, functional studies have suggested that mtDNA oxidative damage under diabetic conditions may trigger a series of pathological events including abnormal mitochondrial gene transcription, uncontrolled oxidative stress, and endothelial dysfunction [12,53], all of which contribute to plaque progression and rupture [54]. In vitro, hyperglycemia may also induce the interaction of mtDNA oxidative damage with inflammatory cytokine release, causing apoptosis of monocytes, T2DM-related endothelial dysfunction, and plaque instability [48].…”
Section: Discussionmentioning
confidence: 99%
“…This result was supported by our further observation that mtDNA 8-OHdG positively correlated with coronary stenosis severity, as determined by the number of diseased vessels and modified Gensini scores. Indeed, functional studies have suggested that mtDNA oxidative damage under diabetic conditions may trigger a series of pathological events including abnormal mitochondrial gene transcription, uncontrolled oxidative stress, and endothelial dysfunction [12,53], all of which contribute to plaque progression and rupture [54]. In vitro, hyperglycemia may also induce the interaction of mtDNA oxidative damage with inflammatory cytokine release, causing apoptosis of monocytes, T2DM-related endothelial dysfunction, and plaque instability [48].…”
Section: Discussionmentioning
confidence: 99%
“…Clones were then tested for TEX264-SSH or SPRTN-SHP*-SSH expression upon induction with 1-1.2 µg/mL Doxycycline by immunoblotting. Flp-In T-Rex-293 cells expressing miRNAs targetting TDP1 were generated as previously described 80 .…”
Section: Methodsmentioning
confidence: 99%
“…If TDP1 reacts more rapidly with a nucleic acid -guanine radical than DMPO, then O 2 y− would be expected to react instead with DMPO. The effect of TDP1 in a cell system, was higher levels of carbon adducts but without the liberation of a peroxyl radical, in TDP1-deficient compared to wild type cells [31]. This, again, would be consistent with the relative hypoxia of cells compared to DNA-melanin in vitro.…”
Section: Discussionmentioning
confidence: 59%